The effect of healthy life approaches applied to families of children in preschool on obesity and healthy life behaviour - Oztoprak Hacioglu, Dilek; Şimşek, Hatice (Progress in Nutrition, 2019)
Aim: The aim of this study was to determine the prevalence and associated factors of obesity and being overweight in 3-5 year-old children attending public kindergarten and develop healthy lifestyle behaviour by applying supportive healthy lifestyle approaches to families with overweight or obese children. Method: The study was composed of two parts: cross-sectional and interventional. The population for the cross-sectional part was 191 children aged between 3-5 and registered to kindergarten, along with and their families. The intervention group accounts for 23 mothers of overweight or obese children diagnosed in the cross-sectional part. Interventions contain counselling interviews, brochures, and letter deliveries showing the weights of their children. Data before and after the intervention were compared. Results: The prevalence of being overweight or obese was 27.2%. It was found out that being overweight or obese was associated with the children’s sex (p=0.034), the mothers’ educational status (p=0.043) as well as the children’s breakfast habits (p=0.009). Following the intervention, positive results were acquired relating to the children’s weight outcomes, their daily average TV, DVD watching duration, and parental behaviour regarding nutrition (p<0.05). Conclusion: It was shown that family-based approaches aiming at the development of healthy lifestyle behaviour in children are effective in preventing and treating obesity.